2020
DOI: 10.1038/s41598-020-74336-x
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular optical doppler phenotypes of chemosensitivity in human epithelial ovarian cancer

Abstract: Development of an assay to predict response to chemotherapy has remained an elusive goal in cancer research. We report a phenotypic chemosensitivity assay for epithelial ovarian cancer based on Doppler spectroscopy of infrared light scattered from intracellular motions in living three-dimensional tumor biopsy tissue measured in vitro. The study analyzed biospecimens from 20 human patients with epithelial ovarian cancer. Matched primary and metastatic tumor tissues were collected for 3 patients, and an addition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…11,47 Diameter measurements are also limited because changes in PCO diameter or morphology often lag behind functional changes. [69][70][71][72] Here we provide the first demonstration of wide-field one-photon redox imaging for functional assessment of drug response in PCOs. Redox imaging improves on existing tools for PCO screening as it is non-destructive, rapid, and label-free, requiring no additional dyes or reagents.…”
Section: Discussionmentioning
confidence: 92%
“…11,47 Diameter measurements are also limited because changes in PCO diameter or morphology often lag behind functional changes. [69][70][71][72] Here we provide the first demonstration of wide-field one-photon redox imaging for functional assessment of drug response in PCOs. Redox imaging improves on existing tools for PCO screening as it is non-destructive, rapid, and label-free, requiring no additional dyes or reagents.…”
Section: Discussionmentioning
confidence: 92%
“…The resistant phenotype is dominated by a mid-frequency enhancement, while the sensitive dogs were more likely to display a mid-frequency suppression with enhance organelle and membrane activities that are representative of apoptosis [401]. A similar study was completed for human ovarian cancer patients [396] and human bladder cancer patients [397]. In both studies, TDS signatures were found to be correlated with patient outcomes.…”
Section: Tissue Dynamics Spectroscopy (Tds)mentioning
confidence: 99%
“…It has also been applied to studies of plasma flow [385,386], dermatology [387], eye drainage [388], and embryology [389][390][391]. For potential use for drug development and diagnostics, dynamic OCT has been used to characterize three-dimensional tissue culture [383,392,393], and for testing chemotherapy cancer drug efficacy in animal preclinical trials [394,395] and in human clinical trials [396,397]. Some of these applications are highlighted in figure 33.…”
Section: Dynamic-contrast Optical Coherence Tomography (Oct)mentioning
confidence: 99%
“…The highly variable character of OCT tissue dynamics spectra among the biopsy samples for a single patient presents an ideal opportunity for deep learning. Our previous work on tissue dynamics of cancer biopsies 5 used averaging approaches which suppressed the conditional dependences. Here, we retain the full well-to-well variability.…”
Section: Deep Learningmentioning
confidence: 99%